Impacto epidemiológico do diabetes mellitus na sobrevivência a síndrome respiratória aguda grave (SRAG) associada a Covid-19: um estudo ecológico - Kurrle, Liege Camargo Alves (2022)
Introduction: In early 2020, the World Health Organization (WHO) declared the disease Coronavirus-2019 (COVID-19), a global pandemic, caused by the infection of the severe acute respiratory syndrome virus coronavirus-2 (SARS-CoV-2). Epidemiological evidence soon indicated that diabetes mellitus (DM) would be an important risk factor (RF) of morbidity and mortality from Severe Acute Respiratory Syndrome (SARS) associated with COVID-19 (SRAG-COVID). However, later evidence suggested that this association would not be universal, requiring additional studies in different countries. Objectives: To assess the epidemiological impact of DM on the evolution of SARS-COVID in patients > 18 years old hospitalized in 2021. Methods: An ecological study was carried out using demographic, cultural, ethnic groups and clinics listed in the SARS Compulsory Notification Form (FN) and made available in the “OpenSus” database (Ministry of Health). Only the FNs correctly filled in as to whether the patient had DM or normoglycemic (NG) were evaluated. Initially, a comparison was made between DM and NG patients regarding the prevalence of: (1) clinical, radiological and tomographic symptoms; (2) admission to intensive care units (ICUs), use of ventilatory support and (3) death. A complementary analysis identified the survival rate (SR) of hospitalized patients with SARS-COVID (with and without a diagnosis of DM) in different federative units (FUs) of Brazil, evaluating the influence of socioeconomic, cultural, sanitation and health care indicators in each state. These indicators were obtained from the Brazilian Institute of Geography Statistics (IBGE), the United Nations Development Program (UNDP), the National Sanitation Information System (SNIS) and Health Assistance (DATASUS, Ministry of Health). Data were presented as relative (%) and/or absolute (n) frequencies, mean ± standard deviation. When necessary, univariate (chi-square test and Spearman correlation) and multivariate (logistic regression) statistical analyzes were performed. Results: 1,048,575 FNs were identified by SARS in 2021, 69% (n=723,525) caused by COVID-19 according to molecular and/or clinical diagnosis. However, only 293,923 (28.0%) were patients who met the inclusion criteria of this study. A total of 142,749 (48.8%) patients had DM. It is possible that this prevalence is overestimated considering the large number of unfilled FNs that were excluded from the analysis. Diabetics had a higher prevalence of clinical symptoms, admission to the ICU and use of ventilatory support. They also had a higher risk of death from SARSCOVID regardless of sex, age, education, self-reported race, previous immunization or presence of other diseases considered RFs for SARS-COVID (Relative risk = 1.117, 95%CI: 1.083-1.152). The survival rate to SARS-COVID hospitalization of both DM and NG patients varied according to the FUs, being positively and moderately correlated with the human development index (HDI, medium, education and longevity), greater number of municipalities with service epidemiological and health surveillance, and a greater supply of high complexity hospitals in each state. Conclusion: Despite the methodological limitations, the results described here indicate that DM is an important risk factor for SARS-COVID mortality in Brazil. These results may be relevant for the development of strategies in primary care aimed at preventing the evolution of SARS-COVID in diabetics.